ESKAPEE pathogens newly released from biofilm residence by a targeted monoclonal are sensitized to killing by traditional antibiotics - Kurbatfinski, Nikola; Kramer, Cameron N.; Goodman, Steven D.; Bakaletz, Lauren O. (Frontiers in Microbiology, 2023)
The ‘silent’ pandemic of antimicrobial resistance (AMR) is responsible for nearly 5 million deaths annually, with a group of 7 biofilm-forming pathogens, known as the ESKAPEE pathogens, responsible for 70% of these fatalities. Biofilm-resident bacteria, as exist within the disease site, are canonically highly antibiotic tolerant. One strategy to both counter AMR and devise better approaches for disease resolution is development of methods to disrupt biofilms to release bacteria from the protective biofilm matrix to facilitate their killing by antibiotics or immune effectors. Several laboratories working on such strategies have demonstrated that bacteria newly released from a biofilm, display a transient phenotype of significantly increased susceptibility to antibiotics. We’ve similarly developed an antibody-based approach for biofilm disruption directed against the two-membered DNABII family of bacterial DNA-binding proteins which serve as linchpins to stabilize the biofilm matrix. Incubation of biofilms with α-DNABII antibodies rapidly collapses the biofilm to induce a population of newly released bacteria (NRel). Here we used a humanized monoclonal antibody (HuTipMab) directed against protective epitopes of a DNABII protein to determine if we could disrupt biofilms formed by the high-priority ESKAPEE pathogens, then demonstrate potentiated killing of the induced NRel by 7 diverse classes of traditional antibiotics. ESKAPEE biofilms were disrupted 50-79% by a single tested dose and treatment period with HuTipMab. NRel of each were significantly more sensitive to killing than even their planktonically grown counterparts (heretofore considered to be the most sensitive to antibiotic-mediated killing), even when tested at a fraction of the MIC (1/250-1/2 MIC). Moreover, killing of bacteria that remained within the biofilms of two representative ESKAPEE pathogens after HuTipMab disruption were now also significantly more susceptible to antibiotic killing. New data presented herein support our continued development of a combinatorial therapy wherein HuTipMab is delivered to a patient with recalcitrant disease due to an ESKAPEE pathogen to disrupt a pathogenic biofilm, along with a co-delivered dose of a now effective antibiotic able to rapidly kill the induced NRel. Ideally, this novel regimen could provide a more successful clinical outcome to those with chronic, recurrent or recalcitrant disease while limiting further contribution to AMR.